Analysis of the Implementation of Restaurant Tax Collection in Increasing Regional Original Revenue of Malang Regency - Hadi Pranoto; Dian Ferriswara; Ika Devy Pramudiana; Sri Kamariyah (Perspektif Administrasi Publik dan hukum, 2025)
This study aims to describe and analyze: The Implementation of Restaurant Tax Collection in Increasing Regional Original Revenue (PAD: Pendapatan Asli Daerah)) of Malang Regency and the Obstacles to the Implementation of Restaurant Tax Collection in Increasing the PAD of Malang Regency. The research is a qualitative descriptive analysis. The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that the Policy on Regional Taxes (specifically Restaurant Tax) in Malang Regency is inseparable from the pattern of fiscal relations between the Central and Regional Governments. This kind of relationship pattern is none other than related to the decentralized policy model that tends to use a top-down approach. The contribution of Restaurant Tax to Regional Taxes during the period 2021-2024 as a whole only reached an average of 5.53%. Although overall from year to year during the 2021-2024 fiscal year period, the contribution of Restaurant Tax to Malang Regency Regional Original Revenue revenue fluctuates, the increase in the realization of Restaurant Tax has been able to help the implementation of local government activities, both routine and development activities. Obstacles to the implementation of restaurant tax collection in increasing the PAD of Malang Regency can be in the form of: a. Low taxpayer awareness: Many restaurant entrepreneurs do not pay taxes or are in arrears of taxes. b. Lack of supervision: Many restaurants or restaurants operate without a license or register. c. Lack of socialization: The public does not know the benefits of paying taxes. d. Lack of bookkeeping: Small and medium-sized restaurants often do not keep bookkeeping. e. Manipulated transactions: Taxpayers deposit, calculate, and pay taxes themselves, resulting in data manipulation